Coaptation Reserve Predicts Optimal Reduction in Mitral Regurgitation and Long-Term Survival With Transcatheter Edge-to-Edge Repair. (10th June 2022) - Sato, Hirotomo; Cavalcante, João L.; Bae, Richard; Bapat, Vinayak N.; Garcia, Santiago; Gössl, Mario; Hashimoto, Go; Fukui, Miho; Enriquez-Sarano, Maurice; Sorajja, Paul
Abstract : Background: Although transcatheter edge-to-edge repair (TEER) is effective and safe, there is a need for better prediction of optimal outcomes. We aimed to determine predictors of optimal reduction in mitral regurgitation (MR) and survival with TEER. Methods: We examined mitral anatomy and its change with TEER on outcomes in 183 patients (age, 82 [77–87] years; 53% women). Coaptation reserve was measured as the distance of continuous apposition of the A2 and P2 leaflet segments in 2-dimensional apical long-axis imaging at the site of the predominant jet of MR. Augmentation in coaptation was measured as the total amount of leaflet insertion. Addressable coaptation area was calculated using the physical boundaries of the TEER device. Results: Coaptation reserve, its augmentation, and addressable coaptation area were strong predictors of MR reduction (all P <0.001), as well as heart failure hospitalization and death. For patients with either mild or no residual MR, median values for coaptation reserve, its augmentation, and addressable coaptation area were 3.7 (2.8–4.5) mm, 7.3 (5.2–9.5) mm, and 59.0 (48.0–71.8) mm 2, respectively. Receiver operating characteristic analyses determined the best values for optimal MR reduction as a coaptation reserve of >3.0 mm ( P <0.001), addressable coaptation area of ≥52 mm 2 ( P <0.001), and coaptation augmentation of ≥4.7 mm ( P <0.001). These values were associated with greater 2-year survival free of all-cause mortality and persisting even in analyses restricted to those with mild or no residual MR after TEER. Conclusions: Coaptation reserve and its augmentation are simple, independent parameters that predict optimal MR reduction and better survival in patients undergoing TEER. These findings may have implications for patient selection and expanded use of the therapy.